Conceptualizing The Floating Court Based On E-Floating Court To Realizing Public Service The Justice System In The Fourth Industrial Revolution Era - Alfedo, Juan Maulana; Yofita, Emilda; Sari, Laras Ayu Lintang (Universitas Negeri Semarang, 2020)
Indonesia is the biggest archipelago in the world with area of 5.9 million km2 with 6.4 million tons of fisheries resources. But with this potential there are still many crimes at sea, one of them is illegal fishing. To overcome various crimes at sea, the government provides the Shipping Court and the Fisheries Court which are expected to fulfill the legal needs of the sea, but in their implementation the two institutions are less than optimal. In the industrial revolution era 4.0, need a means to optimize public services in the justice system, especially in the maritime area. Based on the problem, we established the floating court based on e-floating court which is judicial institution to synergize the performance of shipping court and fisheries court in enforcement of marine law in Indonesia. In this study the authors used a juridical-normative research method.